S1P/S1PR1 signaling is involved in the development of nociceptive pain - Daosong Dong; Xue Yu; Xueshu Tao; Qian Wang; Lin Zhao (Frontiers in Pharmacology, 2024)
BackgroundPain is a complex perception involving unpleasant somatosensory and emotional experiences. However, the underlying mechanisms that mediate its different components remain unclear. Sphingosine-1-phosphate (S1P), a metabolite of sphingomyelin and a potent lipid mediator, initiates signaling via G protein-coupled receptors (S1PRs) on cell surfaces. It serves as a second messenger in cellular processes such as proliferation and apoptosis. Nevertheless, the neuropharmacology of sphingolipid signaling in pain conditions within the central nervous system remains largely unexplored and controversial.MethodsChronic nociceptive pain models were induced in vivo by intraplantar injection of 20 μL complete Freund's adjuvant (CFA) into the left hind paws. We assessed S1P and S1PR1 expression in the spinal cords of CFA model mice. Functional antagonists of S1PR1 or S1PR1-specific siRNA were administered daily following CFA model establishment. Paw withdrawal response frequency (PWF) and paw withdrawal latency (PWL) were measured to evaluate mechanical allodynia and thermal hyperalgesia, respectively. RT-PCR assessed interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF)-α levels. Western blotting and immunofluorescence were used to analyze glial fibrillary acidic protein (GFAP), ionized calcium-binding adapter molecule (Iba1), STAT3, ERK, and p38 MAPK protein expression.ResultsIn the chronic nociceptive pain model induced by CFA, S1P and S1PR1 expression levels were significantly elevated, leading to activation of spinal cord glial cells. S1PR1 activation also promoted MMP2-mediated cleavage of mature IL-1β. Additionally, S1PR1 activation upregulated phosphorylation of STAT3, ERK, and p38 MAPK in glial cells, profoundly impacting downstream signaling pathways and contributing to chronic nociceptive pain.ConclusionThe S1P/S1PR1 axis plays a pivotal role in the cellular and molecular mechanisms underlying nociceptive pain. This signaling pathway modulates glial cell activation and the expression of pain-related genes (STAT3, ERK, p38 MAPK) and inflammatory factors in the spinal dorsal horn. These findings underscore the potential of targeting the S1P system for developing novel analgesic therapies.